Investigating the Impact of Indonesia-Turkey CEPA and Factors influencing Indonesian Export Performance - Arif Darmawan; Muhammad Husaini; Roby Rakhmadi; Ghania Atiqasani (Jurnal Ekonomi Pembangunan, 2022)
The Indonesia-Turkey Comprehensive Economic Partnership Agreement (IT-CEPA) is not solely about a trade agreement between the two countries but is a partnership and collaboration so that the people of the two countries can benefit from bilateral cooperation. This study aims to investigate the impact of IT-CEPA, foreign direct investment (FDI), inflation, natural resource rents, and government effectiveness on Indonesian exports to Turkey. The approach in this study applies a linear regression model from 2000-2020 sourced from the World Bank and The Observatory of Economic Complexity (OEC). The findings of this study indicate that foreign direct investment and government effectiveness have a positive sign and have a significant effect on Indonesian exports to Turkey. Meanwhile, IT-CEPA has a negative and significant sign on Indonesian exports to Turkey. However, inflation and natural resource rents do not have a significant effect on Indonesia's exports to Turkey. The implication of this study is that policy makers must pay attention to governance related to the implementation of economic partnership agreements between Indonesia and trading partner countries, especially in increasing Indonesia's exports to trading partner countries.